Essentialist Biases in Reasoning About Emotions - Berent, Iris; Feldman Barrett, Lisa; Platt, Melanie (Frontiers in Psychology, 2020)
A large literature debates whether emotions are universal and innate. Here, we ask whether reasoning about such matters is shaped by intuitive Essentialist biases that link innateness to the material body. To gauge the perception of innateness, we asked laypeople to evaluate whether emotion categories will be recognized spontaneously by hunter-gatherers who have had no contact with Westerners. Experiment 1 shows that participants believe that emotions are innate and embodied (facially and internally), and these two properties correlate reliably. Experiment 2 demonstrates that the link is causal. When told that emotions are localized in specific brain areas (i.e., embodied), participants concluded that emotions are innate. Experiment 3 shows that this naïve view persists even when participants are explicitly informed that these emotions are acquired. Our results are the first to suggest that laypeople incorrectly believe that, if emotions are embodied, then they must be innate. We suggest that people’s failure to grasp the workings of their psyche arises from the human psyche itself.